Estudo de cosmologia com interação no setor escuro do universo - Lima, Jaelsson Silva (2020)
In this work, a brief introduction to modern cosmology (relativistic cosmology) was made, with the object of study being the cosmology of the dark sector. The study was based on the mathematicaldescriptionofsomespeciﬁcmodelsofinteractionofthedarksectoroftheUniverse: IDEM1, IDEM2 and IDEM4, in order to better describe the nature of dark energy. In addition, the standard modelsΛCDM andωCDM were introduced for comparison purposes. SNe Ia data from the Pantheon sample and H(z) data independent from the cosmological model were used, from measurements performed in ancient cosmic clocks (CC) galaxies, in addition to Baryon Acoustic Oscillations (BAO) and BAO data from extended Baryon Oscillation Spectroscopic Survey (eBOSS).TheanalysisisbasedontheCosmic Linear Anisotropy Solving System (CLASS) code and on the MontePython code using the Markov Chain Monte Carlo (MCMC) method. The ﬁrst refers to the cosmological context, while the second refers to the statistical analysis part to obtain some cosmological parameters of interest. In our work, the results containing data from BAO, BAO(eBOSS) suggest values for H0 around 69kms−1Mpc−1 in all models. From the results of the statistical analysis for each interaction model, overlapping regions were built, in order to identify prohibited regions for the densities of dark energy and dark matter, at some point in its cosmic temporal evolution. The results corroborate the standard model (ΛCDM).